Pasantía proyecto Iflat 63 Seny SAS (2022)
An internship was carried out in the Iflat 63 project of the Seny SAS Construction Company, in the town of Chapinero on Calle 63 # 9-40 Bogotá, several construction processes were worked on, including the structure, gray work and white work, where They handled and carried out quantities of work with their orders. On the other hand, in the development of the administration system, the billing and budget were managed, for which basic concepts were used for the applicability in the development of the activity, additionally, a manageability of the schedule was made where it shows some nonconformities and it was carried out a readjustment in the programming of the work so that its delivery times were met and optimal performance was obtained. Finally, an analysis work was carried out by the work team in which quantities and prices were verified, revealing some flaws in the initial budget and a restructuring of the same was made for delivery to the directors.